A model of an effective materials management for better project performance in construction industry - Mat Jusoh, Zairra (2018)
Materials management plays a significant role in the success of every construction project. However, as a result of ineffective materials management, construction projects have been plagued by poor performances namely time overrun, cost overrun, compromised quality, low productivity and wastage. Thus, to mitigate these issues and concurrently enhance project performance, an effective materials management appears to be a viable solution. Nonetheless, literature review have further highlighted various issues and challenges with materials management implementation in terms of the limited exploration of the factors associated with effectiveness, lack of recognition on its relationship with project performance, and therefore, depicting the need for a new model that incorporates all aspect of materials management. Hence, this study aimed at exploring the factors associated with effective materials management and developing a model as a mechanism to improve this management effectiveness. The quantitative method adopted for data collection involved a survey of 202 practitioners using structured questionnaires. The results of the univariate analysis via SPSS ranked the influential and effect factors. Meanwhile, multivariate analysis using Partial Least Square Structural Equation Modelling (PLS-SEM) technique via SmartPLS 3 tested the relationship between the exogenous construct (influential factors of effective materials management) and endogenous construct (effect factors of project performance). Findings revealed that effective materials management (i.e. transportation, management, purchasing, expediting, site storage and condition, contractual, governmental interference and suppliers) has a significant effect on project performance (i.e. waste, cost, time, productivity and quality). The findings from both analyses were used to develop an effective materials management model for better performance in construction projects. The developed model was evaluated by 28 practitioners to provide feedback on the model’s usability and usefulness. This research model reflects the associated factors in a holistic view as well as integrated all the processes in materials management supply chain that would contribute in enhancing materials management effectiveness. This model also has the capability of assisting in the decision-making process by facilitating an understanding of the influential and effect factors of effective materials management. In conclusion, effective materials management should be implemented in order to enhance better project performance.